PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 038 SEKELADI HILIR KECAMATAN TANAH PUTIH - Harlini, Harlini; Kurniaman, Otang; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the Student Achievement of natural Science SD Negeri 038 Sekeladi Hilir fourth graderes still low with an average value of 62,85 and minimum completeness criteria (KKM) social studies is 70. Between students, amounting to 21 people only 8 students who achieve classical KKM with 38,09%. This research is Classroom Action Research (CAR), which aims to improve the student achievement of natural Science class V at SDN 038 Sekeladi Hilir with implementation Cooperative Learning Model, Type Student Teams Achievement Division (STAD). Formulation of the problem : Is the implementation Cooperative Learning Model, Type Student Teams Achievement Division (STAD) can improve Student Achievement of natural Science at SDN 038 Sekeladi Hilir. The research was conducted on March 18, 2015 to April 15, 2015 by 2 cycles. Subjects were students of SDN 038 Sekeladi Hilir, totaling 21 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 62,85. in the first cycle improve an average 73,33 and an improve in the second with an average of 86,90. Activities of the teacher in the learning process in cycle of 58,33% and the second meeting improve 75%. Cycle II first meeting and the second meeting improve 83,33% and the second meeting improve 87,5%. Results of data analysis of students activities in the first cycle with the first meeting of an average 54,16% and a second meeting improve to 70,83% . Cycle II first meeting improve 79,16% and the second meeting improve to 83,33%. Resultsin the class V at SDN 038 Sekeladi Hilir that the implementation Cooperative Learning Model, Type Student Teams Achievement Division (STAD) can improve Student Achievement of natural Science SDN 038 Sekeladi Hilir.Key Words : Cooperative Learning Model, Type Student Teams Achievement Division